Reduction of Aflatoxins and Microorganisms in the Koura-Koura Produced in Burkina Faso with Spices and Aromatic Leaves - Sawadogo, Yamkaye Aicha; Cisse, Hama; Oumarou, Zongo; Nikiema, Filbert; Traore, Yves; Savadogo, Aly (Journal of Food Technology Research, 2021)
Koura-koura is a product resulting from the processing of peanut. This study consisted of producing koura-koura with garlic, pepper, ginger and mint to reduce aflatoxins and microorganisms. The objective of this work is the decontamination of koura-koura with spices and aromatic leaves. Aflatoxin determination was performed by HPLC and microbiological analyses were carried out according to standard methods. A total of 18 samples were analyzed, including 3 peanut samples, 2 peanut paste samples, 1 koura-koura control sample, and 12 samples of koura-koura spices and aromatic leaves. Total aflatoxin B1, B2, and aflatoxin levels in the samples ranged from 0.58±0.49 μg/kg to 3.66±0.10 μg/kg; 2.23±0.41 μg/kg to 14.02±0.88 μg/kg; 2.87±0.20 μg/kg to 17.75±0.58 μg/kg, respectively. Aflatoxins G1 and G2 were not detected in all samples. The total mesophilic aerobic flora (TMAF) ranged from 1.60±1.57 x101 CFU/g to 4.50±1.28 x105 CFU/g and the yeast and mould flora ranged from 1.80 ± 1.68 x101 CFU/g to 2.80±0.74 x101 CFU/g. No samples were contaminated with thermo-tolerant coliforms and total coliforms were present in a single sample (1.30 ± 1.64 x 101 CFU/g). The results of the study on the reduction of aflatoxins and microorganisms in koura-koura with spices and aromatic leaves contribute significantly to food safety.